Revisiting Rupture of Benign Thyroid Nodules after Radiofrequency Ablation: Various Types and Imaging Features - Sae Rom Chung (Endocrinology and Metabolism, 2019)
BackgroundTo evaluate the imaging features, clinical manifestations, and prognosis of patients with thyroid nodule rupture after radiofrequency ablation (RFA).MethodsThe records of 12 patients who experienced thyroid nodule rupture after RFA at four Korean thyroid centers between March 2010 and July 2017 were retrospectively reviewed. Clinical data evaluated included baseline patient characteristics, treatment methods, initial presenting symptoms, imaging features, treatment, and prognosis.ResultsThe most common symptoms of post-RFA nodule rupture were sudden neck bulging and pain. Based on imaging features, the localization of nodule rupture was classified into three types: anterior, posterolateral, and medial types. The anterior type is the most often, followed by posterolateral and medial type. Eight patients recovered completely after conservative treatment. Four patients who did not improve with conservative management required invasive procedures, including incision and drainage or aspiration.ConclusionThyroid nodule rupture after RFA can be classified into three types based on its localization: anterior, posterolateral, and medial types. Because majority of thyroid nodule ruptures after RFA can be managed conservatively, familiarity with these imaging features is essential in avoiding unnecessary imaging workup or invasive procedures.